The mindful tourist : the power of presence in tourism - Stankov, Ugljesa; Gretzel, Ulrike; Filimonau, Viachaslau (The tourist experience, 2022)
The Mindful Tourist presents the first comprehensive theoretical perspective on mindfulness in contemporary tourist experiences. This innovative new study is based on the detailed exploration of mindful consumer behaviour and draws on insights from new cases of mindful tourism experiences, examining the potential for broader uptake across the industry. Examining the foundations of meditative mindfulness practices, mindfulness and tourism, the mindful tourism experience, and transformational power of mindful tourism experiences, The Mindful Tourist: The Power of Presence in Tourism explores key themes and issues, including the drivers of mindfulness in the tourism domain, the commodification of mindfulness, mindfulness and sustainability, and mindful tourist experiences being assisted through technology.